Răspuns :
1. a) (2x²-3x+5)+(-6x²+4x-1 )
Renuntam la paranteze
= 2x²-3x+5-6x²+4x-1
= -4x²-3x+5+4x-1
= -4x²+x+5-1
= -4x²+x+4
b) (-x²+5x-1)-(2x²+x-3)
Renuntam la paranteze
= -x²+5x-1-2x²-x+3
= -3x²+5x-1-x+3
= -3x²+4x-1+3
= -3x²+4x+2
c) 3x*(x+1)+(x³-6x²+5x):x
= 3x²+3x+x³-6x²+5x/x
= 3x²+3x+x*(x²-6x+5)/x
= 3x²+3x+x²-6x+5
= 4x²+3x-6x+5
= 4x²-3x+5
Renuntam la paranteze
= 2x²-3x+5-6x²+4x-1
= -4x²-3x+5+4x-1
= -4x²+x+5-1
= -4x²+x+4
b) (-x²+5x-1)-(2x²+x-3)
Renuntam la paranteze
= -x²+5x-1-2x²-x+3
= -3x²+5x-1-x+3
= -3x²+4x-1+3
= -3x²+4x+2
c) 3x*(x+1)+(x³-6x²+5x):x
= 3x²+3x+x³-6x²+5x/x
= 3x²+3x+x*(x²-6x+5)/x
= 3x²+3x+x²-6x+5
= 4x²+3x-6x+5
= 4x²-3x+5